THE CORRELATION OF KNOWLEDGE, PPE AVAILABILITY, TRAINING, SUPERVISION AND WORK STRESS WITH WORKER OBEDIENCE TO WORKING AT HIGH SOP (Study in Apartment Construction Project PT. X , Semarang) - Andrew William; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat, 2019)
Abstract : Obedience is an act that in line with commands and rules, which is processed trough believe, receive and action. Based on Lawrence Green’s Behavioral Theory, obedience is influenced by predisposing factor, enabling factor and reinforcing factor. Working at high SOP violation case, unsafe act and unsafe condition that can cause mental fatigue. The purpose of this research is to analyze the correlation of work related stress, knowledge, PPE availability, training and supervision with worker obedience to working at high SOP in construction site. The type of this research is a cross-sectional study using quantitative method.The population in this research were 44 high area workers. The sample in this research were 44 high area worker with total sampling technique.The instruments in this research were using Depression Anxiety Stress Scale 21 (DASS 21) to measure the work stress and other questionare to measure the knowledge level, PPE avaliability, training and supervision. The statistical analysis that used is Fisher’s Exact test. The result showed that there was a correlation of work related stress (p value = 0,001) and training (p value = 0,049) , but no correlation of knowledge (p value = 0,738) , PPE availability (p value = 0,488) and supervision (p value = 0,231) with worker obedience to working at high SOP. Researcher suggest to decrease the level of work related stress by providing lite sport games facility, and provide sign to remind the worker about SOP obedience.